Utility of modified endoscopic radial incision and selective cutting combined with short-term stenting for refractory stricture in patients undergoing endoscopic submucosal dissection of superficial esophageal carcinoma - Lu Chen; Xiajiao Tang; Jingjing Jiang; XiaoChun Yin; Yuxin Wang; Mingyue Li; Ruihua Shi (Therapeutic Advances in Gastroenterology)
Background: Refractory esophageal stricture is the common complication of extensive endoscopic submucosal dissection (ESD), without satisfactory endoscopic treatment strategies. We evaluated the efficacy, safety, and long-term patency of the modified endoscopic radial incision and selective cutting combined with short-term stenting (RISC-STS) for the treatment of refractory esophageal stenosis. Methods: This was a retrospective study. Patients diagnosed with refractory esophageal stricture from June 2016 to June 2023 were enrolled. Efficacy, safety, and risk factors for dysphagia after RISC-STS operation were assessed. Results: Compared with clinical symptoms before RISC-STS, there was no significant improvement in the times of stricture recurred ( p  = 0.75). However, the narrowest diameter of esophageal stenosis was significantly larger after RISC-STS treatment ( p  = 0.04). Corresponding dysphagia scores after RISC-STS were obviously lowered according to the Mellow–Pinkas grading scale ( p  = 0.002). More cases ((14 (60.87%) vs 5 (21.74%)) received valid symptom-relief periods after RISC-STS ( p  = 0.0004). The complications of RISC-STS include perforation (4.35%), fever (4.35%), and pain (30.43%). Univariate Cox analysis suggested that resection length >7 cm of scar tissue was a risk factor for refractory dysphagia after RISC-STS. Conclusion: The present study revealed that RISC-STS is an effective and safe technique for refractory esophageal stricture with lower restenosis, higher valid symptom-relief rate, and fewer complications.